Suspect identities : a history of fingerprinting and criminal identification - Cole, Simon A., 1967- (Harvard University Press, 2002)
"Cole excavates the forgotten and hidden history of criminal identification--from photography to exotic anthropometric systems based on measuring body parts, from fingerprinting to DNA typing"--Jacket